Structural equation modeling applied to assess industrial engineering students’ satisfaction according to ENADE 2011 - Agenor Sousa Santos Neto; Maria José Pereira Dantas; Ricardo Luiz Machado (Production)
Abstract This research aims to propose and try out a model to assess the Industrial Engineering students’ satisfaction, with a focus on private higher education institutions. The research tool used in this study was the Student Questionnaire 2011 National Exam for the Assessment of Student Performance (ENADE), made available by the Brazilian Ministry of Education (MEC). The questions were designed to assess undergraduate students general satisfaction based on the following constructs: Teacher Involvement, Student Interest, Course Demands, Course Organization, and General Satisfaction. A new construct was added to this research: Infrastructure. The methods employed to analyze students’ responses concerning their satisfaction with the service provided by higher education institutions were: Confirmatory Factor Analysis and Structural Equation Modeling, with the support of the software package SPSS® (Statistical Package for the Social Sciences) and the AMOS® module. The hypotheses proposed in the model indicate that the construct Teacher Involvement is key to Student General Satisfaction.